The Effect of Coorporate Governance on Financial Performance in Food and Beverage Sub Sector Manufacturing Listed on The Indonesian Stock Exchange - Alfiana Alfiana; Iwan S Seber; Rustan Rustan; Adindah Novihartina Jafar; Sahari Sahari; Andi Arifwangsa Adiningrat (International Journal of Economics Development Research (IJEDR), 2023)
There are various problems with the company's financial performance that can affect the company's stability, profitability and growth. One of the key factors that can support improving a company's financial performance is the implementation of a good corporate governance system or what is often referred to as corporate governance. Strong corporate governance can help create a transparent, accountable and efficient environment, which in turn can improve the Company's financial performance. This research aims to determine and analyze the influence of financial governance on financial performance in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. The type of data in this research is secondary data from the Indonesian Stock Exchange in the 2020-2022 financial reports. The data analysis method in this research is quantitative data with the help of the SPSS 25 application with analysis of the t test, f test and coefficient of determination test. The research results show that corporate governance (the independent board of commissioners, board of directors, managerial ownership and institutional ownership) simultaneously have no effect and are not significant on financial performance of manufacturing companies listed on the Indonesia Stock Exchange